Vietnam’s Geopolitical Strategy: Assessing the Perceived Implications of the Cancelled 2020 Grand Prix - Passakorn Indraruna (International Journal of Asia Pacific Studies, 2026)
The cancellation of the 2020 Vietnamese Grand Prix, initially planned as a flagship of Vietnam’s geopolitical ambition, constituted a major disruption to the country’s soft power strategy. Rather than interpreting the cancellation solely as a logistical setback, this study frames it as a diagnostic moment for assessing Vietnam’s institutional capacity for resilience and strategic diplomacy. Using a mixed-methods design that combines document analysis, a stakeholder survey (n = 97), and thirty semi-structured interviews, this study examines how the event’s termination shaped stakeholder perceptions of Vietnam’s soft power and international reputation. Statistical analyses (analysis of variance [ANOVA] and regression) and thematic coding reveal that while stakeholders recognised the event’s strategic intent, the cancellation highlighted significant coordination gaps and a “narrative vacuum”. This study introduces and operationalises the concept of “exit diplomacy” – the strategic capacity to narrate a withdrawal to preserve reputational capital. Comparative insights from Singapore and Malaysia further highlight the strategic divergence between resilience, managed withdrawal, and silence. Results indicate that while government officials prioritised long-term resilience planning, the private sector expressed higher economic anxiety and emphasised the need for soft power diversification. This study concludes that for emerging middle-powers, the ability to curate a withdrawal narrative is as critical to soft power resilience as the capacity to host. Finally, five actionable strategies are proposed, including the establishment of an Event Resilience Unit within the Ministry of Culture, Sports and Tourism.